INVENTARIO PRELIMINAR DE LAS PLANTAS UTILIZADAS PARA ELABORAR ARTESANIAS EN COLOMBIA - Linares C., Edgar L.; Herbario. Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
Plants used in the elaboration of crafL<>manships in our Country play an important role in the economy of the rural communities and ofthe craftmen ofthe urban zones. The results obtaincd up until now includc 248 species distributed in 175 genera and 66 familics. 770 common names corresponding to 299 names in 33 indigenous languages and 4 71 popular names were registered and 134 uses or artisanal products were described. Dicotyledons are important to obtain woods (83), fruits, seeds (25) and barks (36). Monocotyledons provide fibers obtaincd from lcaves, spats, bracts and shoots (34), stems and culms (34) and roots (14).